Lack of artemisinin resistance in Plasmodium falciparum in northwest Benin after 10 years of use of artemisinin-based combination therapy - Ogouyèmi-Hounto, A.; Damien, A.B.; Deme, A.B.; Ndam, N.T.; Assohou, C.; Tchonlin, D.; Mama, A.; Hounkpe, V.O.; Moutouama, J.D.; Remoué, F.; Ndiaye, D.; Gazard, D.K. (My University, 2016)
Aim: In Benin, artemisinin-based combination therapy (ACT) has been recommended as the first-line treatment for uncomplicated Plasmodium falciparum malaria since 2004. The emergence in Southeast Asia of parasites that are resistant to artemisinins poses a serious threat to global control of this disease. The presence of artemisinin resistance genotypes in parasite populations in Benin is currently unknown. The present study investigated the prevalence of relevant K13-propeller gene polymorphisms in parasite isolates from the north-western region of Benin. Method: Plasmodium falciparum isolates were collected from children with a confirmed diagnosis of malaria aged 6 months to 5 years in two towns, Cobly and Djougou, in the north-western part of Benin. The study was conducted during the rainy season from July to November 2014 in local health facilities. The K13-propeller gene was amplified in parasite isolates using nested PCR and subsequently sequenced. Results: A total of 108 children were recruited into the study. The efficiency of amplification reactions was 72% (78/108). The propeller domain of the K13 gene was successfully sequenced in 78 P. falciparum isolates; all of them were wild type with no polymorphisms detectable. Conclusion: The absence of mutations in the K13 gene indicates that P. falciparum parasite populations in the study area are still fully susceptible to artemisinins. © 2016 A. Ogouyèmi-Hounto et al., published by EDP Sciences.
Keywords: Artemisinin; Benin; K13; propeller; Malaria; Plasmodium; falciparum; Resistance